1995
DOI: 10.1002/cm.970310106
|View full text |Cite
|
Sign up to set email alerts
|

Topographic compensation: Guidance and directed locomotion of fibroblasts on grooved micromachined substrata in the absence of microtubules

Abstract: Fibroblasts cultured on grooved substrata align themselves and migrate in the direction of the grooves, a phenomenon called contact guidance. Microtubules have been deemed important for cell polarization, directed locomotion, and contact guidance. Because microtubules were the first cytoskeletal element to align with the grooves when fibroblasts spread on grooved substrata, we investigated the consequences of eliminating the influence of microtubules by seeding fibroblasts onto smooth and grooved micromachined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…Nonetheless, fibroblasts have been reported to align along grooves and ridges before wellformed actin filaments were observed (Oakley and Brunette, 1993;Walboomers et al, 2000). Additionally, contact guidance, albeit delayed, has been observed to occur in the presence of poisons that disrupt the actin cytoskeleton in fibroblasts (Oakley and Brunette, 1995b;Oakley et al, 1997;Walboomers et al, 2000;Wojciak-Stothard et al, 1995a). We therefore conclude that focal adhesion and microfilament alignment is not a prerequisite for contact guidance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Nonetheless, fibroblasts have been reported to align along grooves and ridges before wellformed actin filaments were observed (Oakley and Brunette, 1993;Walboomers et al, 2000). Additionally, contact guidance, albeit delayed, has been observed to occur in the presence of poisons that disrupt the actin cytoskeleton in fibroblasts (Oakley and Brunette, 1995b;Oakley et al, 1997;Walboomers et al, 2000;Wojciak-Stothard et al, 1995a). We therefore conclude that focal adhesion and microfilament alignment is not a prerequisite for contact guidance.…”
Section: Discussionmentioning
confidence: 67%
“…However, the detection of actin condensations along the groove/ridge boundaries 5 minutes after cell adhesion suggested that actin aggregation rather than microtubule alignment is the first and primary event in the contact guidance mechanism (Wojciak-Stothard et al, 1995a). Nonetheless, contact guidance was observed in cells cultured on micrometer-wide grooves and ridges where either the microtubule or the microfilament (Oakley and Brunette, 1995b;Oakley et al, 1997;Walboomers et al, 2000;Wojciak-Stothard et al, 1995a) systems were disrupted by cytoskeletal poisons. Interestingly, when submicrometer features were investigated (500 nm wide grooves and ridges), functional microtubules were found to be necessary to induce contact guidance (Oakley et al, 1997).…”
mentioning
confidence: 99%
“…Interested in the biocompatibility and performance of dental implants, Brunette's group [77][78][79][80] has extensively studied topographic guidance of cultured human gingival fibroblasts on titanium-coated micromachined silicon wafers or epoxy replicas. Fibroblast aligned both within the micromachined grooves and on the intervening fl at ridges and transmission electron microscopy showed that the cellular cytoskeleton oriented in the same fashion.…”
Section: Effect Of Microtopography On Fibroblastmentioning
confidence: 99%
“…Thus the grooved substratum compensated for the microtubule deficiency by organizing and maintaining an aligned actin filament framework. 79 Further experiments showed that the dimensions of the groovesinfluenced the kinetics of cell alignment. An unexpected finding was that very narrow (0.5 μm wide and 0.5 μm deep) grooves aligned cells deficient in actin microfilament bundles (cytochalasin B-treated) better than untreated control cells but failed to align cells deficient in microtubules (colcemid-treated).…”
Section: Effect Of Microtopography On Fibroblastmentioning
confidence: 99%
“…As expected, it is mainly the expression of myosin genes and of genes coding for associated proteins, as well as other motor proteins, that are regulated in our experiments. We are currently not able to address any signalling function for dynein and kinesin, but they function as transporters along microtubules and are co-localized with or linked to actin fibres via further linker molecules, respectively (Oakley and Brunette, 1995). Two potential pathways are leading to ECM formation in hearts of renal failure Whereas most of the collagens and proteoglycans are upregulated during the first days after operation, in the 12 w group a striking upregulation of laminins, together with integrins, is noted.…”
Section: Motor Proteins Play a Potential Role In Signal Translationmentioning
confidence: 99%